(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It addresses waste management from a life cycle and circular economy perspective, demonstrating its high potential for emission reduction and advocating for its centrality in the discussions of the Paris Agreement and COP-30. (Received: September 2025 | Accepted: October 2025)